Strategi Brand Relationship Quality Pada Bisnis Waralaba di Indonesia - Andressia Yeiza Putri; Rusnandari Retno Cahyani (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
A franchise is defined as a business that provides more or special benefits. Based on the results of literature research, franchise marketing can be a consideration to be implemented by paying attention to the standards of the brand owners with whom we collaborate. Franchise marketing can bring new colors and develop attractive, quality products at more affordable prices. BRQ strategy is a method for establishing a high-quality psychological or emotional connection between consumers and brands. The focus of this research examines the things that need to be prepared to use the BRQ strategy to build a franchise business in Indonesia. The method used in this article is narrative literature reflection and literature search based on research conducted in Indonesia. Literature search using the Google Scholar database.